Cognitive conflict as a tool of overcoming obstacles in understanding infinity - Cihlář, Jiří; Eisenmann, Petr; Krátká, Magdalena; Vopĕnka, Petr (Teaching Mathematics and Computer Science, 2009)
This paper, based on current research, is devoted to obstacles that appear in the process of understanding the concept of infinity. In its introductory part the fundamental types of epistemology obstacles are formulated. The cognitive conflict and its role in overcoming these obstacles are analysed in the following section of this research. Finally, the authors focus on research methodology and the results of the three-year research project. The problems are illustrated by means of real experimental interviews.